Menstrual management in transgender and gender diverse individuals: psychiatric and psychosocial considerations - Arshed, Arslaan; Madanes, Sharon; Pottinger, Stephanie; Ackerman, Marra G.; Deutch, Allison B. (Frontiers in Psychiatry, 2024)
Transgender and gender-diverse (TGD) menstruators are individuals assigned female at birth (AFAB)*, who retain the capacity to menstruate and have a gender identity that differs from their natal sex. Reports indicate up to 1.6 million individuals in the US identify as TGD. Until recently, the mainstream menstrual discourse has failed to capture the experience of transmenstruators. However, a better understanding of the menstrual experiences of TGD-AFAB will allow for more individualized patient-centered care. In this review, we provide the relevant data necessary to inform the psychiatric management of menstruation in TGD-AFAB individuals, including experiences of menstruation, preferences for menstrual management, and the impact on mental health. Our review indicates that menstrual care in TGD patients must be tailored to the individual; clinicians should remain open-minded to the unique experience of transmenstruators; gender-affirming menstrual care is necessary to reduce psychological burden. It should not be assumed that TGD-AFAB menstruators are utilizing appropriate contraceptive methods and should receive contraceptive and fertility preservation counseling. We highlight the importance of having these conversations early in the reproductive arch, even before puberty onset. Keeping in mind the gender minority stress model, in the upcoming sections, we discuss the limited body of literature on mood disorders in TGD-AFAB individuals who menstruate, undergo menstrual suppression, or continue to ovulate. The psychological impact of hormonal therapies is also reviewed.